ANALISIS USAHATANI TALAS TAIWAN (Colocasia esculenta var. Taiwan) (Studi Kasus : di Kelompok Tani Saluyu I RW.01 Kelurahan Situgede Kecamatan Bogor Barat Kota Bogor) - Denden Dilah Al zikri; Herawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Taro is one of Bogor's typical agricultural commodities. One type of taro planted is taroTaiwan. The high demand for Taiwan's taro commodity (Colocasia esculensta var. Taiwan) fromTaiwan and Thailand, then sent the Taiwanese taro commodity (Colocasia esculensta var. Taiwan)planting commodities wider. This study aimed to analyze the system of processing, largeproduction and productivity, substancial net income, and economic analysis review of taiwan tarofarm commodities in Saluyu Farmer Group 1 Situgede Village, West Bogor District, Bogor City,West Java Province. The research method involves taking sample by using census method, datacollection taken from secondary and primary data, data analysis using the formula π = TR-TC(net income), R / C Ratio to measure the feasibility of farming economically. The system of processing taiwan taro farming carried out in the area of research in the form of land preparation,planting, fertilizing, and landfill that still relatively modest yet as recommended by the literature(according to Hodijah, 2009). The average production taiwan taro farm amounted to 3.526 piecesand productivity of 19.420,26 pieces/ha is still low compared to the literature (SEAMEOBIOTROP Research Bogor West Java). Total net income taiwan taro farm during one growingseason is Rp248.790.000, -. Analysis of R/C ratio is 13,95 taiwan taro farm therefore the farmingis economically very feasible to be developed (R / C ≥ 1).